Here,

Let initial mass of the first body be M

initial mass of the second body be m

initial distance between them be d

Then, initial gravitational force of attraction between two bodies is given by:

\(F_i=\frac{GMm}{d^2}=\) --------- (1)

Now according to the question,

final mass of the first body is 2M (mass is doubled)

final mass of the second body is 2m

find distance between them is 3d (distance is tripled)

so, final gravitational force of attraction between them is

\(F_f=\frac{G\times2M\times2m}{{(3d)}^2}\) ---------- (2)

Or, \(F_f=\frac{6\times GMm}{9d^2}\)

Or, \(F_f=\frac69\frac{GMm}{d^2}\)

Or, \(F_f=\frac69F_i\)

Or, \(F_f=\frac23F_i\)

This imples that the final force will reduces by two third compared to initial force.